Apolipoprotein J/Clusterin Prevents a Progressive Glomerulopathy of Aging - Rosenberg, Mark E. (American Society for Microbiology, 2002)
Apoliprotein J (apoJ)/clusterin has attracted considerable interest based on its inducibility in multiple injury processes and accumulation at sites of remodeling, regression, and degeneration. We therefore sought to investigate apoJ/clusterin's role in kidney aging, as this may reveal the accumulated effects of diminished protection. Aging mice deficient in apoJ/clusterin developed a progressive glomerulopathy characterized by the deposition of immune complexes in the mesangium. Up to 75% of glomeruli in apoJ/clusterin-deficient mice exhibited moderate to severe mesangial lesions by 21 months of age. Wild-type and hemizygous mice exhibited little or no glomerular pathology. In the apoJ/clusterin-deficient mice, immune complexes of immunoglobulin G (IgG), IgM, IgA, and in some cases C1q, C3, and C9 were detectable as early as 4 weeks of age. Electron microscopy revealed the accumulation of electron-dense material in the mesangial matrix and age-dependent formation of intramesangial tubulo-fibrillary structures. Even the most extensively damaged glomeruli showed no evidence of inflammation or necrosis. In young apoJ/clusterin-deficient animals, the development of immune complex lesions was accelerated by unilateral nephrectomy-induced hyperfiltration. Injected immune complexes localized to the mesangium of apoJ/clusterin-deficient but not wild-type mice. These results establish a protective role of apoJ/clusterin against chronic glomerular kidney disease and support the hypothesis that apoJ/clusterin modifies immune complex metabolism and disposal.